A high thermal conductivity epoxy resin composition based on copper clad laminate and preparation method thereof

By mixing hexagonal boron nitride with epoxy resin and modifying polydopamine, the thermal conductivity and flame retardant properties of the epoxy resin composition are improved, and the problems of low thermal conductivity and flammability of existing epoxy resins are solved. Meet the heat dissipation needs of copper clad plates to work at high frequencies and reduce fire risks.

CN118725518BInactive Publication Date: 2025-02-07NANTONG RODA ELECTRON
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410966566.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing epoxy resin has low thermal conductivity and is easy to burn, making it difficult to meet the heat dissipation needs of copper clad plates when working at high frequencies, and there is a fire hazard.

Method used

By mixing hexagonal boron nitride with epoxy resin and modifying by polydopamine, the compatibility and interface binding force of boron nitride with epoxy resin are improved, thereby improving thermal conductivity and improving flame retardant through grafting reaction performance.

Benefits of technology

It significantly improves the thermal conductivity and flame retardant properties of the epoxy resin composition, meets the heat dissipation needs of copper clad plates working at high frequencies, and reduces fire risk.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004951936750000101
    Figure BDA0004951936750000101
  • Figure BDA0004951936750000111
    Figure BDA0004951936750000111
Patent Text Reader

Abstract

The present invention relates to the technical field of epoxy resins, specifically to a high thermal conductivity epoxy resin composition based on copper clad laminates and a preparation method thereof. The present invention uses hexagonal boron nitride as a filler, and is mixed with epoxy resin, diluent, epoxy toughening agent, coupling agent, defoamer, and antioxidant to prepare an epoxy resin composition; Boron nitride is modified by polydopamine to improve the compatibility of boron nitride and epoxy resin, enhance the interfacial bonding force, so that the thermal resistance of the epoxy resin composition is reduced, and the thermal conductivity is improved; In order to further improve the flame retardant properties of the epoxy resin composition, the present invention uses 4-hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide as raw materials to prepare a flame retardant, and the flame retardant is grafted onto polydopamine-modified boron nitride by phosphorus oxychloride to achieve the flame retardant modification of boron nitride. The epoxy resin composition prepared by the present invention has a large thermal conductivity and good flame retardant properties, which meets the production needs of copper clad laminates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of epoxy resins, and in particular to a high thermal conductivity epoxy resin composition based on a copper clad laminate and a preparation method thereof. Background Art

[0002] Copper clad laminate is the abbreviation of copper foil laminate, which is the base material for processing printed circuit boards. It has become an indispensable component of most electronic products. The preparation method of copper clad laminate is to soak electronic fiberglass cloth or other reinforcing materials in resin liquid, cover one or both sides with copper foil and make a plate-shaped composite material through hot pressing process. Epoxy resin has the advantages of good bonding performance, high mechanical strength, good electrical insulation and small curing shrinkage, so it is widely used in copper clad laminate.

[0003] With the continuous development of technology, electronic devices are becoming increasingly miniaturized and are constantly developing in the direction of being thinner, more integrated, and more high-frequency. Due to the high packaging density of electronic devices, the heat generated per unit volume will increase significantly when working at high frequencies, and the accumulated heat will seriously affect the operating reliability of electronic devices, becoming a key factor limiting the working life of electronic devices. However, due to the low thermal conductivity of epoxy resin, it is difficult to meet the application requirements of copper clad laminates at this stage. In addition, epoxy resin is extremely flammable, and its poor heat dissipation performance also poses a hidden danger of combustion, which will not only burn electronic devices, but also easily cause fires. Therefore, it is very necessary to develop a high thermal conductivity epoxy resin composition based on copper clad laminates. Summary of the invention

[0004] The object of the present invention is to provide a high thermal conductivity epoxy resin composition based on copper clad laminate and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high thermal conductivity epoxy resin composition based on copper clad laminate and a preparation method thereof, comprising the following steps:

[0006] Step 1:

[0007] Mix 4-hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, introduce nitrogen for protection, heat to 180-190° C., react for 3-5 hours, cool to 100-110° C., filter, wash and dry to obtain a flame retardant;

[0008] Step 2:

[0009] S1: mixing tris(hydroxymethylaminomethane) hydrochloride buffer with anhydrous ethanol to obtain a mixed solution;

[0010] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 15 to 30 minutes, dispersing the hexagonal boron nitride in the mixed solution, and obtaining a boron nitride dispersion solution; adding dopamine hydrochloride to the boron nitride dispersion solution, and reacting at 25 to 30° C. for 2 to 3 hours; filtering and collecting the precipitate after the reaction is completed, adding the precipitate to deionized water, centrifuging, freeze-drying, and grinding to obtain polydopamine-modified boron nitride;

[0011] Step 3:

[0012] The flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixed material; the mixed material is dispersed in pyridine and nitrogen is introduced for protection; the mixture is stirred and heated to 60-65° C., kept warm for 0.5-1 h, triethylamine is added as an acid binding agent, and the mixture is heated to 100-105° C., refluxed for 8-12 h, and after the reaction is completed, filtered, washed and dried to obtain flame retardant modified boron nitride;

[0013] Step 4:

[0014] The epoxy resin, diluent, epoxy toughening agent, coupling agent, defoaming agent, antioxidant and flame retardant modified boron nitride are mixed, and after stirring for 10 to 15 minutes, a curing agent and a curing agent accelerator are added to obtain an epoxy resin composition.

[0015] Furthermore, in step 1, 4-hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are reacted in a molar ratio of 1:(2-3).

[0016] Furthermore, in S1, the tris(hydroxymethyl)aminomethane hydrochloride buffer solution and anhydrous ethanol are mixed in a volume ratio of (3-4):1.

[0017] Furthermore, in S1, the pH of the Tris hydrochloride buffer solution is 8-9.

[0018] Furthermore, in S2, the weight ratio of dopamine hydrochloride to boron nitride is (15-25):100.

[0019] Furthermore, in step 3, the mixed material contains, by weight percentage, 92-95% of polydopamine-modified boron nitride, and the remainder is flame retardant and phosphorus oxychloride.

[0020] Furthermore, in step 3, in the mixed material, the molar ratio of phenolic hydroxyl group in the flame retardant to phosphorus oxychloride is (1-2):1.

[0021] Furthermore, in step 4, the contents of the components in the epoxy resin composition are, by weight, 25 to 30 parts of epoxy resin, 6 to 8 parts of diluent, 3 to 5 parts of epoxy toughening agent, 0.5 to 1 part of coupling agent, 0.3 to 0.5 part of defoaming agent, 0.2 to 0.5 part of antioxidant, 10 to 20 parts of flame retardant modified boron nitride, 20 to 24 parts of curing agent, and 0.5 to 0.8 part of curing agent accelerator.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] The present invention uses hexagonal boron nitride as a filler, mixes it with epoxy resin, and obtains an epoxy resin composition. Hexagonal boron nitride is an artificially synthesized inorganic material, and its stacking mode is similar to that of graphite, and it also has high thermal conductivity similar to that of graphene. However, the surface of boron nitride is inert. On the one hand, it has poor compatibility with epoxy resin, and is easily agglomerated after being physically blended with epoxy resin, and is unevenly dispersed in epoxy resin; on the other hand, the heat conduction process occurs between fillers and at the interface between fillers and resin matrix. The weak interface bonding force between boron nitride and resin matrix leads to defects at the interface, and the thermal resistance increases, which affects the overall modification effect. After boron nitride is modified by polydopamine, agglomeration of boron nitride is avoided; polydopamine contains active groups such as phenolic hydroxyl and amino groups in its structure, which can participate in the polymerization reaction of epoxy resin, and introduces boron nitride into the molecular chain segment of epoxy resin, which not only improves the compatibility of boron nitride with epoxy resin, but also greatly enhances the interface bonding force between filler and resin, so that thermal resistance is reduced and thermal conductivity is improved.

[0024] Boron nitride itself does not burn, but its flame retardant effect in epoxy resin is not ideal. The present invention uses 4-hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide as raw materials to prepare a flame retardant containing phenolic hydroxyl groups, and uses phosphorus oxychloride as a bridge to graft the flame retardant onto polydopamine-modified boron nitride. Boron nitride can inhibit the combustion diffusion rate of epoxy resin, thereby achieving a synergistic flame retardant effect with the flame retardant. Phosphorus oxychloride can react with the phenolic hydroxyl groups on the flame retardant, the phenolic hydroxyl groups on the surface of boron nitride, and the amino groups. Since the activity of the amino groups is stronger than that of the phenolic hydroxyl groups, in the early stage of the reaction, part of the phosphorus oxychloride will preferentially react with the amino groups and be grafted onto the boron nitride. As the reaction proceeds, the number of amino groups that can be grafted on the boron nitride decreases, and the phosphorus oxychloride begins to react and graft with the phenolic hydroxyl groups on the surface of the boron nitride. At the same time, the ungrafted phosphorus oxychloride will combine with the phenolic hydroxyl groups in the flame retardant. If the three chlorines in the ungrafted phosphorus oxychloride react with the phenolic hydroxyl groups in the flame retardant, the flame retardant cannot be grafted onto the surface of the boron nitride, resulting in a reduced grafting rate and a decrease in flame retardant performance. Therefore, during the reaction, the present invention controls the molar ratio of the phenolic hydroxyl groups of the flame retardant to the phosphorus oxychloride to be (1-2):1, thereby increasing the grafting rate of the flame retardant.

[0025] In addition, during the actual research and development process, the inventors found that the polydopamine loaded on the surface of boron nitride also affects the performance of the product. When the polydopamine content is high, the grafting rate of the flame retardant increases and the flame retardant effect is enhanced, but the polydopamine and flame retardant on the surface of the boron nitride will also form thermal resistance, resulting in a decrease in the flame retardant effect. Therefore, after repeated experiments, when preparing polydopamine-modified boron nitride, the weight ratio of dopamine hydrochloride and boron nitride is controlled to (15-25):100, and the thermal conductivity of the epoxy resin composition obtained is greater than 1W / (m·k), and the limiting oxygen index is greater than 27%. Both thermal conductivity and flame retardancy meet the production needs of copper clad laminates. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Materials used in the present invention and their sources: epoxy resin comes from Sinopec Hunan Petrochemical Co., Ltd., model E51; epoxy toughener comes from Shandong Riko Chemical Co., Ltd., model ACM-24; diluent is n-butyl glycidyl ether; coupling agent is KH560; defoamer comes from Henan Henglande Environmental Protection Technology Co., Ltd., model JK-8601; antioxidant is antioxidant 1010; curing agent is methyltetrahydrophthalic anhydride; curing agent accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; hexagonal boron nitride (particle size 1-2μm) comes from Dandong Rijin Technology Co., Ltd.

[0028] Embodiment 1: A high thermal conductivity epoxy resin composition based on copper clad laminate and a preparation method thereof, comprising the following steps:

[0029] Step 1:

[0030] 4-Hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed in a molar ratio of 1:2, nitrogen is introduced for protection, the mixture is heated to 180°C, reacted for 3 hours, cooled to 100°C, filtered, washed and dried to obtain a flame retardant;

[0031] Step 2:

[0032] S1: mixing a pH 8.5 tris(hydroxymethylaminomethane) hydrochloride buffer solution and anhydrous ethanol in a volume ratio of 3:1 to obtain a mixed solution;

[0033] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 15 minutes, so that the hexagonal boron nitride is dispersed in the mixed solution to obtain a boron nitride dispersed solution; adding dopamine hydrochloride to the boron nitride dispersed solution, reacting at 25°C for 2 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water, centrifuging for 3 times, freeze-drying and grinding to obtain polydopamine-modified boron nitride; wherein the weight ratio of dopamine hydrochloride to boron nitride is 25:100;

[0034] Step 3:

[0035] A flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixture, wherein the mixture contains 92% polydopamine modified boron nitride by weight, and the remainder is the flame retardant and phosphorus oxychloride, wherein the molar ratio of phenolic hydroxyl group and phosphorus oxychloride in the flame retardant is 2:1; the mixture is dispersed in pyridine, nitrogen is introduced for protection, the mixture is stirred and heated to 60°C, kept warm for 0.5h, triethylamine is added as an acid binding agent, the mixture is continuously heated to 100°C, refluxed for 8h, and after the reaction is completed, filtered, washed and dried to obtain flame retardant modified boron nitride;

[0036] Step 4:

[0037] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 10 g of flame retardant modified boron nitride were mixed, and after stirring for 10 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0038] Embodiment 2: A high thermal conductivity epoxy resin composition based on copper clad laminate and a preparation method thereof, comprising the following steps:

[0039] Step 1:

[0040] 4-Hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed in a molar ratio of 1:2, nitrogen is introduced for protection, the mixture is heated to 185°C, reacted for 4 hours, cooled to 105°C, filtered, washed and dried to obtain a flame retardant;

[0041] Step 2:

[0042] S1: mixing a pH 8.5 tris(hydroxymethylaminomethane) hydrochloride buffer solution and anhydrous ethanol in a volume ratio of 3:1 to obtain a mixed solution;

[0043] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 20 minutes, so that the hexagonal boron nitride is dispersed in the mixed solution to obtain a boron nitride dispersed solution; adding dopamine hydrochloride to the boron nitride dispersed solution, reacting at 30°C for 2.5 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water, centrifuging for 3 times, freeze-drying and grinding to obtain polydopamine-modified boron nitride; wherein the weight ratio of dopamine hydrochloride to boron nitride is 15:100;

[0044] Step 3:

[0045] A flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixed material, wherein the mixed material contains 92% polydopamine modified boron nitride by weight, and the remainder is the flame retardant and phosphorus oxychloride, wherein the molar ratio of phenolic hydroxyl group and phosphorus oxychloride in the flame retardant is 2:1; the mixed material is dispersed in pyridine, nitrogen is introduced for protection, the mixture is stirred and heated to 65° C., kept warm for 1 hour, triethylamine is added as an acid binding agent, the mixture is continuously heated to 100° C., refluxed for 10 hours, and after the reaction is completed, filtered, washed and dried to obtain flame retardant modified boron nitride;

[0046] Step 4:

[0047] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 10 g of flame retardant modified boron nitride were mixed, and after stirring for 13 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0048] Embodiment 3: A high thermal conductivity epoxy resin composition based on copper clad laminate and a preparation method thereof, comprising the following steps:

[0049] Step 1:

[0050] 4-Hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed in a molar ratio of 1:2, nitrogen is introduced for protection, the mixture is heated to 190° C., reacted for 5 hours, cooled to 110° C., filtered, washed and dried to obtain a flame retardant;

[0051] Step 2:

[0052] S1: mixing a pH 8.5 tris(hydroxymethylaminomethane) hydrochloride buffer solution and anhydrous ethanol in a volume ratio of 3:1 to obtain a mixed solution;

[0053] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 30 minutes, so that the hexagonal boron nitride is dispersed in the mixed solution to obtain a boron nitride dispersed solution; adding dopamine hydrochloride to the boron nitride dispersed solution, reacting at 30°C for 3 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water, centrifuging for 3 times, freeze-drying and grinding to obtain polydopamine-modified boron nitride; wherein the weight ratio of dopamine hydrochloride to boron nitride is 15:100;

[0054] Step 3:

[0055] A flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixture, wherein the mixture contains 92% polydopamine modified boron nitride by weight, and the remainder is the flame retardant and phosphorus oxychloride, wherein the molar ratio of phenolic hydroxyl group and phosphorus oxychloride in the flame retardant is 2:1; the mixture is dispersed in pyridine, nitrogen is introduced for protection, the mixture is stirred and heated to 65° C., kept warm for 1 hour, triethylamine is added as an acid binding agent, the mixture is continuously heated to 100° C., refluxed for 11 hours, and after the reaction is completed, filtered, washed and dried to obtain flame retardant modified boron nitride;

[0056] Step 4:

[0057] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 10 g of flame retardant modified boron nitride were mixed, and after stirring for 14 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0058] Embodiment 4: A high thermal conductivity epoxy resin composition based on copper clad laminate and a preparation method thereof, comprising the following steps:

[0059] Step 1:

[0060] 4-Hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed in a molar ratio of 1:2, nitrogen is introduced for protection, heated to 180°C, reacted for 3 hours, cooled to 110°C, filtered, washed and dried to obtain a flame retardant;

[0061] Step 2:

[0062] S1: mixing a pH 8.5 tris(hydroxymethylaminomethane) hydrochloride buffer solution and anhydrous ethanol in a volume ratio of 3:1 to obtain a mixed solution;

[0063] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 25 minutes, so that the hexagonal boron nitride is dispersed in the mixed solution to obtain a boron nitride dispersed solution; adding dopamine hydrochloride to the boron nitride dispersed solution, reacting at 25°C for 3 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water, centrifuging for 3 times, freeze-drying and grinding to obtain polydopamine-modified boron nitride; wherein the weight ratio of dopamine hydrochloride to boron nitride is 15:100;

[0064] Step 3:

[0065] A flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixture, wherein the mixture contains 92% polydopamine modified boron nitride by weight, and the remainder is the flame retardant and phosphorus oxychloride, wherein the molar ratio of phenolic hydroxyl group and phosphorus oxychloride in the flame retardant is 2:1; the mixture is dispersed in pyridine, nitrogen is introduced for protection, the mixture is stirred and heated to 60°C, kept warm for 0.5h, triethylamine is added as an acid binding agent, the mixture is continuously heated to 100°C, refluxed for 12h, and after the reaction is completed, filtered, washed and dried to obtain flame retardant modified boron nitride;

[0066] Step 4:

[0067] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 14 g of flame retardant modified boron nitride were mixed, and after stirring for 15 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0068] Embodiment 5: A high thermal conductivity epoxy resin composition based on copper clad laminate and a preparation method thereof, comprising the following steps:

[0069] Step 1:

[0070] 4-Hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed in a molar ratio of 1:2, nitrogen is introduced for protection, the mixture is heated to 190° C., reacted for 5 hours, cooled to 100° C., filtered, washed and dried to obtain a flame retardant;

[0071] Step 2:

[0072] S1: mixing a pH 8.5 tris(hydroxymethylaminomethane) hydrochloride buffer solution and anhydrous ethanol in a volume ratio of 3:1 to obtain a mixed solution;

[0073] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 20 minutes, so that the hexagonal boron nitride is dispersed in the mixed solution to obtain a boron nitride dispersed solution; adding dopamine hydrochloride to the boron nitride dispersed solution, reacting at 25°C for 2.5 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water, centrifuging for 3 times, freeze-drying and grinding to obtain polydopamine-modified boron nitride; wherein the weight ratio of dopamine hydrochloride to boron nitride is 15:100;

[0074] Step 3:

[0075] A flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixture, wherein the mixture contains 92% polydopamine modified boron nitride by weight, and the remainder is the flame retardant and phosphorus oxychloride, wherein the molar ratio of phenolic hydroxyl group and phosphorus oxychloride in the flame retardant is 2:1; the mixture is dispersed in pyridine, nitrogen is introduced for protection, the mixture is heated to 60°C with stirring, and the mixture is kept warm for 1 hour, triethylamine is added as an acid binding agent, the mixture is heated to 100°C continuously, and the mixture is refluxed for 9 hours, and after the reaction is completed, the mixture is filtered, washed and dried to obtain flame retardant modified boron nitride;

[0076] Step 4:

[0077] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 17 g of flame retardant modified boron nitride were mixed, and after stirring for 15 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0078] Embodiment 6: A high thermal conductivity epoxy resin composition based on copper clad laminate and a preparation method thereof, comprising the following steps:

[0079] Step 1:

[0080] 4-Hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed in a molar ratio of 1:2, nitrogen is introduced for protection, the mixture is heated to 190° C., reacted for 3 hours, cooled to 105° C., filtered, washed, and dried to obtain a flame retardant;

[0081] Step 2:

[0082] S1: mixing a pH 8.5 tris(hydroxymethylaminomethane) hydrochloride buffer solution and anhydrous ethanol in a volume ratio of 3:1 to obtain a mixed solution;

[0083] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 30 minutes, so that the hexagonal boron nitride is dispersed in the mixed solution to obtain a boron nitride dispersed solution; adding dopamine hydrochloride to the boron nitride dispersed solution, reacting at 30°C for 3 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water, centrifuging for 3 times, freeze-drying and grinding to obtain polydopamine-modified boron nitride; wherein the weight ratio of dopamine hydrochloride to boron nitride is 15:100;

[0084] Step 3:

[0085] A flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixture, wherein the mixture contains 92% polydopamine modified boron nitride by weight, and the remainder is the flame retardant and phosphorus oxychloride, wherein the molar ratio of phenolic hydroxyl group to phosphorus oxychloride in the flame retardant is 2:1; the mixture is dispersed in pyridine, nitrogen is introduced for protection, the mixture is stirred and heated to 65° C., kept warm for 1 hour, triethylamine is added as an acid binding agent, the mixture is continuously heated to 105° C., refluxed for 9 hours, and after the reaction is completed, filtered, washed and dried to obtain flame retardant modified boron nitride;

[0086] Step 4:

[0087] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 20 g of flame retardant modified boron nitride were mixed, and after stirring for 10 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0088] Comparative Example 1: No flame retardant modified boron nitride was added, and other parameters were the same as those in Example 1.

[0089] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 10 g of boron nitride were mixed, and after stirring for 10 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0090] Comparative Example 2: The amount of the flame retardant in step 3 was increased, and the other parameters were the same as those in Example 2.

[0091] Step 1:

[0092] 4-Hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed in a molar ratio of 1:2, nitrogen is introduced for protection, the mixture is heated to 185°C, reacted for 4 hours, cooled to 105°C, filtered, washed and dried to obtain a flame retardant;

[0093] Step 2:

[0094] S1: mixing a pH 8.5 tris(hydroxymethylaminomethane) hydrochloride buffer solution and anhydrous ethanol in a volume ratio of 3:1 to obtain a mixed solution;

[0095] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 20 minutes, so that the hexagonal boron nitride is dispersed in the mixed solution to obtain a boron nitride dispersed solution; adding dopamine hydrochloride to the boron nitride dispersed solution, reacting at 30°C for 2.5 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water, centrifuging for 3 times, freeze-drying and grinding to obtain polydopamine-modified boron nitride; wherein the weight ratio of dopamine hydrochloride to boron nitride is 15:100;

[0096] Step 3:

[0097] A flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixture, wherein the mixture contains 92% polydopamine modified boron nitride by weight, and the remainder is the flame retardant and phosphorus oxychloride, wherein the molar ratio of phenolic hydroxyl group and phosphorus oxychloride in the flame retardant is 3:1; the mixture is dispersed in pyridine, nitrogen is introduced for protection, the mixture is heated to 65° C. with stirring, and the mixture is kept warm for 1 hour, triethylamine is added as an acid binding agent, the mixture is heated to 100° C. continuously, and the mixture is refluxed for 10 hours, and after the reaction is completed, the mixture is filtered, washed and dried to obtain flame retardant modified boron nitride;

[0098] Step 4:

[0099] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 10 g of flame retardant modified boron nitride were mixed, and after stirring for 13 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0100] Comparative Example 3: The amount of dopamine hydrochloride in step S2 was increased, and the other parameters were the same as those in Example 3.

[0101] Step 1:

[0102] 4-Hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed in a molar ratio of 1:2, nitrogen is introduced for protection, the mixture is heated to 190° C., reacted for 5 hours, cooled to 110° C., filtered, washed and dried to obtain a flame retardant;

[0103] Step 2:

[0104] S1: mixing a pH 8.5 tris(hydroxymethylaminomethane) hydrochloride buffer solution and anhydrous ethanol in a volume ratio of 3:1 to obtain a mixed solution;

[0105] S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 30 minutes, so that the hexagonal boron nitride is dispersed in the mixed solution to obtain a boron nitride dispersed solution; adding dopamine hydrochloride to the boron nitride dispersed solution, reacting at 30°C for 3 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water, centrifuging for 3 times, freeze-drying and grinding to obtain polydopamine-modified boron nitride; wherein the weight ratio of dopamine hydrochloride to boron nitride is 30:100;

[0106] Step 3:

[0107] A flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixture, wherein the mixture contains 92% polydopamine modified boron nitride by weight, and the remainder is the flame retardant and phosphorus oxychloride, wherein the molar ratio of phenolic hydroxyl group and phosphorus oxychloride in the flame retardant is 2:1; the mixture is dispersed in pyridine, nitrogen is introduced for protection, the mixture is stirred and heated to 65° C., kept warm for 1 hour, triethylamine is added as an acid binding agent, the mixture is continuously heated to 100° C., refluxed for 11 hours, and after the reaction is completed, filtered, washed and dried to obtain flame retardant modified boron nitride;

[0108] Step 4:

[0109] 25 g of epoxy resin, 8 g of diluent, 4 g of epoxy toughening agent, 1 g of coupling agent, 0.3 g of defoaming agent, 0.4 g of antioxidant, and 10 g of flame retardant modified boron nitride were mixed, and after stirring for 14 minutes, 20 g of curing agent and 0.5 g of curing agent accelerator were added to obtain an epoxy resin composition.

[0110] Experiment: The epoxy resin compositions in Examples 1 to 6 and Comparative Examples 1 to 3 were made into strips: the epoxy resin compositions were mechanically stirred and ultrasonically dispersed at 40°C for 60 minutes, then poured into a preheated stainless steel mold, vacuum degassed at 80°C until there were no bubbles in the solution, and then cured at normal pressure. The curing process was 80°C / 2h+150°C / 4h, and the sample obtained by demoulding was polished to obtain a strip. The performance of the strips was tested, and the experimental results are shown in the following table. Among them:

[0111] Thermal conductivity: The test was conducted using a thermal conductivity meter (Netzsch Instrument Manufacturing Co., Ltd., Germany, model LFA467) using the flash laser method.

[0112] Flame retardant performance: tested using an oxygen index instrument, sample size 130×6.5×3.2mm 3 .

[0113]

[0114]

[0115] Conclusion: The data of Examples 1 to 6 show that the epoxy resin composition prepared by the present invention has good performance and can be used in the preparation of copper-clad laminates. The data of Example 1 and Comparative Example 1 show that the flame-retardant modified boron nitride prepared by the present invention significantly improves the thermal conductivity and flame retardancy of epoxy resin; the data of Example 2 and Comparative Example 2 show that when the amount of flame retardant in step 3 is increased, the grafting rate of flame retardant and polydopamine-modified boron nitride is significantly reduced, and the flame retardant effect is not good; the data of Example 3 and Comparative Example 3 show that when the amount of dopamine hydrochloride is increased, more polydopamine coating is formed on the surface of boron nitride, and the thermal resistance increases, resulting in a decrease in thermal conductivity and poor thermal conductivity.

[0116] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity epoxy resin composition based on a copper clad laminate, characterized in that: The following steps are involved: Step 1: S1: mixing tris(hydroxymethylaminomethane) hydrochloride buffer with anhydrous ethanol to obtain a mixed solution; S2: adding hexagonal boron nitride to the mixed solution, ultrasonically treating for 15 to 30 minutes, dispersing the hexagonal boron nitride in the mixed solution, and obtaining a boron nitride dispersion solution; adding dopamine hydrochloride to the boron nitride dispersion solution, and reacting at 25 to 30° C. for 2 to 3 hours; filtering and collecting the precipitate after the reaction, adding the precipitate to deionized water for centrifugation, freeze-drying, and grinding to obtain polydopamine-modified boron nitride; the weight ratio of dopamine hydrochloride to boron nitride is (15 to 25):100; Step 2: The flame retardant, phosphorus oxychloride and polydopamine modified boron nitride are mixed to obtain a mixed material; the mixed material is dispersed in pyridine and nitrogen is introduced for protection; the mixture is stirred and heated to 60-65° C., kept warm for 0.5-1 h, triethylamine is added as an acid binding agent, and the mixture is heated to 100-105° C., refluxed for 8-12 h, and after the reaction is completed, filtered, washed and dried to obtain flame retardant modified boron nitride; The preparation method of the flame retardant comprises: mixing 4-hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, introducing nitrogen for protection, heating to 180-190° C., reacting for 3-5 hours, cooling to 100-110° C., filtering, washing and drying to obtain the flame retardant; wherein 4-hydroxy-benzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are reacted in a molar ratio of 1:(2-3); In the mixed material, by weight percentage, 92-95% of polydopamine modified boron nitride, the remainder of which is a flame retardant and phosphorus oxychloride, and the molar ratio of phenolic hydroxyl group and phosphorus oxychloride in the flame retardant is (1-2):1; Step 3: The epoxy resin, diluent, epoxy toughening agent, coupling agent, defoamer, antioxidant and flame retardant modified boron nitride are mixed, and after stirring for 10 to 15 minutes, a curing agent and a curing agent accelerator are added to obtain an epoxy resin composition; The content of each component in the epoxy resin composition, by weight, is 25 to 30 parts of epoxy resin, 6 to 8 parts of diluent, 3 to 5 parts of epoxy toughening agent, 0.5 to 1 part of coupling agent, 0.3 to 0.5 part of defoaming agent, 0.2 to 0.5 part of antioxidant, 10 to 20 parts of flame retardant modified boron nitride, 20 to 24 parts of curing agent, and 0.5 to 0.8 part of curing agent accelerator.

2. The method for preparing a high thermal conductivity epoxy resin composition based on a copper clad laminate according to claim 1, characterized in that: In S1, tris(hydroxymethylaminomethane) hydrochloride buffer and anhydrous ethanol are mixed in a volume ratio of (3-4):

1.

3. The method for preparing a high thermal conductivity epoxy resin composition based on a copper clad laminate according to claim 1, characterized in that: In S1, the pH of the Tris hydrochloride buffer solution is 8-9. 4 . The epoxy resin composition prepared by the preparation method according to claim 1 .

Citation Information

Patent Citations

  • Flame-retardant synthetic resin composition

    CN105209551A

  • Flame-retardant and aging-resistant epoxy resin glass fiber reinforced plastic for shell of four-wheel electric vehicle

    CN108752872A